Annual runoff and erosion in a recently burn Mediterranean forest – The effects of plowing and time-since-fire - Vieira, D. C. S. (2020)
The impacts of forest fires on runoff and soil erosion have been assessed by many studies, so the effects of fires on the hydrological and geomorphological processes of burnt forest areas, globally and in the Mediterranean region, are well established. Few studies, however, have assessed post-fire runoff and erosion on large time scales. In addition, a limited number of studies are available that consider the effect of pre-fire land management practices on post-fire runoff and erosion. This study evaluated annual runoff and sediment losses, at micro plot scale, for 4 years after a wildfire in three eucalypt plantations with different pre-fire land management practices (i.e., plowed and unplowed). During the four years following the fire, runoff amounts and coefficients at the downslope plowed (1257 mm, 26%) and contour plowed eucalypt sites (1915 mm, 40%) were higher than at the unplowed site (865 mm, 14%). Sediment losses over the 4 years of study were also consistently higher at the two plowed sites (respectively, 0.47 and 0.83 Mg ha− 1 y− 1 at the downslope and contour plowed eucalypt site) than at the unplowed site (0.11 Mg ha− 1 y− 1). Aside from pre-fire land management, time-since-fire also seemed to significantly affect post-fire annual runoff and erosion. In general, annual runoff amounts and erosion rates followed the rainfall pattern. Runoff amounts presented a peak during the third year of monitoring while erosion rates reached their maximum one year earlier, in the second year. Runoff coefficients increased over the 4 years of monitoring, in disagreement to the window of disturbance post-fire recovery model, but sediment concentrations decreased over the study period. When compared with other long-term post-fire studies and with studies evaluating the effects of pre- and post-fire management practices, the results of the present work suggest that an ecosystem's recovery after fire is highly dependent on the background of disturbances of each site, as runoff and erosion values were higher at the plowed sites than at the unplowed site.